LU_GERICHTE 21 05 16.1 vom 11. August 2005 - LU Gerichte (2005)
§§ 129 und 158 f. StPO; Art. 6 Ziff. 1 und 3 lit. a EMRK; Art. 32 Abs. 2 BV. Grundsätzliche Erwägungen zum Anklageprinzip. | Strafprozessrecht